HUMAN CAPITAL AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Wardani, Erlita Kusuma (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2022)
Introduction: The competitiveness of the workforce in Indonesia is currently still relatively low compared to several ASEAN countries such as Thailand, Malaysia, and Singapore. One of the main factors of this problem is the level of education possessed by the workforce. The construction services sector is a sector that can leverage the country's economy. Thus, the construction sector requires skilled, superior, and reliable workers. The competence and level of education possessed by the workforce will be an important consideration for companies in the construction sector. The purpose of this study is to find out how the influence of Human Capital and Job Satisfaction on Employee Performance. Methods: This study uses a quantitative method with a simple regression method. The sample of this research is as many as 42 respondents of CV Gunung Emas Mahameru project employees. Results: The results showed that the variable Human Capital and Job Satisfaction had a significant effect on employee performance. This is the main capital that is needed by the company in order to improve performance towards a more optimal and efficient direction. Conclusion and suggestion: The biggest company's capital is employees. Human capital is an important element that must be owned by the company. If the company's employees have good competence, it will create high productivity for the company.